The Use of Technology in Accounting Classrooms During COVID-19: What Do Accounting Teachers in the Eastern Cape, South Africa, Have to Say? - Melikhaya Skhephe; Martha Matashu (Research in Social Sciences and Technology, 2021)
It was mentioned that accounting classrooms must keep pace with rapidly changing technology, which is influencing all aspects of our daily lives. This study examined accounting teachers’ views on the use of technology in their classrooms during Covid-19. To this end, the researchers employed a qualitative approach and a case study. Data were obtained from accounting teachers through interviews, with the sample of ten participants having been purposively selected. The results indicated that allowing learners to bring their own personal technological devices to the classroom represented a contravention of the school’s constitution. Another result was that when technology is optimally used in the classroom, it makes available different forms of assistance which change the way learners learn. Researchers conclude that use of technology in accounting implemented compulsory if teachers want to keep up with changes accounting profession. Furthermore, schools’ constitutions need to be amended to promote the use of available technologies in the classroom, albeit in a highly structured, managed, and efficient way. Researchers recommend that learners be allowed to use their own personal devices in the classroom, to enhance learning. School principal be encouraged to develop school plans outlining how s/he would support use of technology in school.